Utilization of micrometeorology to measure carbon assimilation and the transpiration of sugar cane - García-Delgado, M.A. (Universidad Autónoma de Tamaulipas, 2010)
Since august 2008 until the year in course, the evaluation of the effect of algaenzims in the assimilation of carbon dioxide and the sugar cane transpiration with the utilization of a micrometeorologic scientific instrument and the latest technology is in course. this type of study is the first done at a national level, this study is happening in a located in the “y griega” from Xicotencatl-ingenio “Aaron Saenz Garza”, in Xicotencatl, Tamaulipas.